Karyological Notes for Seven Salvia L. Taxa Grown in Turkey - Gedik, Osman; Kiran, Yasar; Emre, Irfan; Kursat, Murat (Univ Tokyo Cytologia, 2016)
This study presents a more detailed karyological analysis of seven Salvia L. taxa (S. ceratophylla, S. syriaca, S. palaestina, S. aethiopis, S. russellii, S. multicaulis, S. trichoclada) grown in Turkey. Also, this is the first chromosome number report for S. russellii and S. trichoclada. This study revealed that the chromosome numbers of the examined Salvia taxa were 2n=14, 18, 22 and 32. The Salvia taxa had median point (M), median (m), submedian (sm) and subterminal (st) chromosomes in the study. Furthermore, various karyotype asymmetry values, ploidy levels, karyotype formula, chromosome length range, total karyotype length, A1, A2 and Stebbins classification were determined in this study. On the other hand, Pearson correlations between the karyotype asymmetries of these Salvia taxa were determined and a dispersion diagram was formed by using A1 and A2. Furthermore, this study suggested that the examined Salvia taxa were 2A and only S. trichoclada was 3A.
Keywords: Chromosome number; Karyotype assymetry; Salvia; Stebbins' classification